One-dimensional seismic velocity model and 3D tomographic features of the Southern Caribbean of Costa Rica - Arroyo, Ivonne (2021)
In 1991, the Southern Caribbean of Costa Rica was the setting of the latest large earthquake (Mw 7.7) between the Caribbean plate and the Panama microplate. Despite the high seismicity and advances in seismic network coverage, this area lacks detailed tomographic images. Using the VELEST and SIMULPS packages, we derive the one-dimensional and three-dimensional velocity models resulting from the inversion of 1208 earthquakes recorded between 1998 and 2020 by the National Seismological Network (RSN). This new tomography shows a band of low velocities that inclines towards the southwest down to depths of 50 km below Talamanca, including the hypocenter of the Limon earthquake and seismicity down to 30 km. This configuration is interpreted as the subduction of the Caribbean plate under the Panama microplate and the Limon earthquake as an interplate seismogenic zone event. The determined geometry provides a new framework for interpreting the complex tectonics of southeastern Costa Rica.